Integrated Filtered Web-Search Engine - Wan Abd Kadir, Wan Nordiana (Universiti Teknologi Petronas, 2006)
WWW has become one of the most important sources of information. WWW is not an indexed information warehouse where people easily look for specifieddata; it is instead a large collection of network of computers that contains the information. Finding informationin the WWWcan be as easy as it can be hard. Search engine was developed to assist users in searching information on the net. There exist a number of available effective search engine in the market nowadays but where human are concerns they always have something that they are not satisfied with. Mass information supplied to the users might get them exhausted as they browse through eachand every oneofthe results returned. Even so, there were users who have the habits of only look at the top 10 of the results page and will go to another search engine if there still not satisfied with the information. This project aims to reduce users dilemma on mass information supplied as well as to combine the major search engines normally used by most users nowadays. The benefits are that users can have more results from various search engines with one single click without any redundant results.